Neutralization of SARS-CoV-2 Variants by mRNA and Adenoviral Vector Vaccine-Elicited Antibodies - Tada, Takuya; Zhou, Hao; Samanovic, Marie I.; Dcosta, Belinda M.; Cornelius, Amber; Herati, Ramin S.; Mulligan, Mark J.; Landau, Nathaniel R. (Frontiers in Immunology, 2022)
The increasing prevalence of SARS-CoV-2 variants has raised concerns regarding possible decreases in vaccine effectiveness. Here, neutralizing antibody titers elicited by mRNA-based and an adenoviral vector-based vaccine against variant pseudotyped viruses were measured. BNT162b2 and mRNA-1273-elicited antibodies showed modest neutralization resistance against Beta, Delta, Delta plus and Lambda variants whereas Ad26.COV2.S-elicited antibodies from a significant fraction of vaccinated individuals had less neutralizing titer (IC50 <50). The data underscore the importance of surveillance for breakthrough infections that result in severe COVID-19 and suggest a potential benefit by second immunization following Ad26.COV2.S to increase protection from current and future variants.